The Influence Of Quality Of Work Life On The Performance Of Nurses At Majene Regency General Hospital - Muhammad Takwa; Andi Niartiningsih; Nurul Hidayah Nur; Nurfitriani Nurfitriani; Mene Paradilla; Iqbal Mochtar (International Journal of Health and Medicine, 2024)
One thing that hospitals must consider is the performance of nurses. Performance is the achievement or result in terms of quality and quantity of an employee for their work in accordance with the directions and responsibilities given by their superiors. The aim of this research is to analyze the influence of Quality of Work Life on the Performance of Inpatient Installation Nurses at Majene Regency General Hospital. The research method uses a quantitative approach using an analytical observational design with a cross sectional approach, sampling was carried out using random sampling of 85 respondents. The population in this study were all nurses with employee status who provided services and were on duty in the Inpatient Room at Majene Regency General Hospital, namely 134 people. The results of the research show that there is an influence on the variable quality of work life based on the work life dimension with a p value of 0.008 < 0.05, work world with a p value of 0.001 < 0.05, work context with a p value of 0.004 < 0.05, and work design with a p value 0.013<0.05. It is recommended that hospital management improve the Quality of Work Life for nurses by revising the system for distributing compensation for medical services, improving and the work environment security system.